Mechanisms underlying the methylglyoxal-induced enhancement of uridine diphosphate-mediated contraction in rat femoral artery - Takayuki Matsumoto; Madoka Yoshioka; Aiko Yamada; Kumiko Taguchi; Tsuneo Kobayashi (Elsevier, 2022)
Although femoral artery dysfunctions, including aberrant vascular reactivity to vasoactive substances, are common in many chronic disorders, such as diabetes and hypertension, their inducible and/or progressive factors remain unclear. Methylglyoxal (MGO), a highly reactive dicarbonyl compound, has been implicated in the pathogenesis of various chronic disorders. However, its direct correlation with extracellular nucleotides including uridine 5'-diphosphate (UDP) in the femoral artery function is currently unknown. Therefore, we investigated the acute effect of MGO on UDP-induced contraction in the rat femoral artery. MGO (4.2 × 10−4 M for 1 h) enhanced the UDP-induced contraction. This enhancement was not abolished in all conditions, including nitric oxide synthase inhibition, cyclooxygenase inhibition, or endothelial denudation. In the endothelium-denuded arteries, the p38 mitogen-activated protein kinase (MAPK) inhibitor SB203580 (10−5 M) suppressed the UDP-induced contraction in both control and MGO-treated groups, while MGO enhanced the p38 MAPK activation regardless of the UDP presence. Moreover, in the endothelium-denuded arteries, the Syk tyrosine kinase inhibitor piceatannol (10−5 M) suppressed the UDP-induced contraction. These results suggest that MGO augments UDP-induced contraction in rat femoral arteries and that this may be partly due to the alterations in the activities of Syk tyrosine kinase and p38 MAPK in the smooth muscle.